The Government of Catalonia and the Pyrenees-Mediterranean Euroregion - Cortadelles i Bacaria, Àngel (Documents d’Anàlisi Geogràfica, 2010)
The globalization phenomena experienced during the 20th century, along with the European integration process, shape an essentially different scenario for the development of international relations in the 21st century, and, in a more special and concrete way, for local political action within the European framework.